Determinação da Precisão Intermediária de um Espectrômetro de Massas de Altíssima Resolução e Exatidão em Análise de Petróleos - Folli, Gabriely Silveira (2020)
The ultrahigh resolution and mass accuracy from electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry, ESI(±)FT-ICR MS, makes it possible to discern very close m/z (mass/charge ratio) signals. This differentiation capacity is